2015
DOI: 10.1111/trf.13229
|View full text |Cite
|
Sign up to set email alerts
|

Type of plasma preparation used for plasma exchange and clinical outcome of adult patients with acquired idiopathic thrombotic thrombocytopenic purpura: a French retrospective multicenter cohort study

Abstract: The outcomes of acquired TTP treated with S/D plasma or qFFP seem similar and therefore both preparations can be used safely for PE in this indication. The faster response of S/D plasma observed in younger patients warrants confirmation in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
(43 reference statements)
0
21
1
2
Order By: Relevance
“…Cardiac adverse events were the antecedent cause of death in only one QP patient (nodal rhythm, bradycardia and cardiac arrest). Mortality was not substantially different from that reported in other studies .…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…Cardiac adverse events were the antecedent cause of death in only one QP patient (nodal rhythm, bradycardia and cardiac arrest). Mortality was not substantially different from that reported in other studies .…”
Section: Discussioncontrasting
confidence: 74%
“…The size of the study population was limited by the low frequency of auto‐immune TTP. Both types of plasma provided remission rates consistent with those reported for primary idiopathic TTP with conventional plasma . Multiple secondary efficacy outcomes were similar between treatment groups.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Pooling has the added benefit of diluting allergens by approximately 1000‐fold, which reduces the risk of allergic reactions. Multiple studies have shown a comparative reduction in the rate of allergic reactions (Table ) . Pooling likely mitigates the risk of TRALI by diluting and neutralizing antibodies to human neutrophil antigen and HLA.…”
Section: Session 2: Implementation Of Prt For Blood Products In the Umentioning
confidence: 99%